Lessons on early structure formation from a mature galaxy cluster observed at cosmic noon. Issue 2 (11th May 2020) - Liu, Boyuan; Schauer, Anna T P; Bromm, Volker
ABSTRACT: We demonstrate a new approach of indirectly constraining both early star and structure formation via mature galaxy clusters at cosmic noon ( z ∼ 2), using the cluster XLSSC 122 as an example. With the standard Press Schechter formalism, we infer a rapid evolution of the star formation efficiency (the ratio of stellar to halo mass) from 10 −4 to 0.01 during z ∼ 20−13, based on the age distribution of stars in post-starburst galaxies of XLSSC 122, measured by Hubble Space Telescope photometry assuming no dust extinction. Here, we consider all low-mass haloes, including minihaloes, that host the first stars and galaxies ($5× 10^5\ \rm M_{\odot }\lesssim M_{\rm halo}\lesssim 10^{10}\ \rm M_{\odot }$ ). We also place new constraints on fuzzy dark matter models of m a ≲ 5 × 10 −21 eV/ c 2 for the ultralight boson mass, from the abundance of galaxies with star formation at z ≳ 13 in XLSSC 122. Our exploratory results are consistent with existing constraints. More comprehensive results will be obtained if our approach is extended to a large sample of clusters or field post-starburst galaxies at cosmic noon, with improved modelling of halo and stellar populations.